Investasi Reksadana Syariah pada Aplikasi Bareksa dalam Perspektif Fikih Muamalah - Ahmad Mubarak; Khaerul Aqbar; Fadhlan Akbar (AL-QIBLAH: Jurnal Studi Islam dan Bahasa Arab, 2023)
This study aims to determine sharia mutual fund investment in the bareksa application in the muamalah fiqh perspective. The type of research used in this research is library research with a normative juridical approach. The results of the study show that: (1) the law of origin of sharia mutual fund investment is permissible (mubah) as long as there is no argument against it and does not conflict with Islamic law; (2) the contract used in the sale and purchase of sharia mutual funds in the bareksa application is the sale and purchase of salam, in which the buyer enters into a waka>lah and mudarabah contract; (3) Bareksa can be used as an alternative for investing because it has several advantages, both in terms of data transparency, ease of investment which is very helpful for buyers of Islamic mutual funds, managed by experienced experts and practical and flexible investment facilities.